2011
DOI: 10.3844/ajavsp.2011.130.134
|View full text |Cite
|
Sign up to set email alerts
|

Quails Response to Aqueous Extract of Bush Marigold (<i>Aspilia africana</i>) Leaf

Abstract: Problem statement:The effects of inclusion of aqueous extract of Bush marigold (Aspilia africana) leaf in quail diet were investigated. One hundred and fifty Japanese quail chicks were used in the study. Approach: In the 14-weeks feeding experiment, the birds were assigned to five treatments of; 0, 2.5, 5.0, 7.5 and 10% inclusion of aqueous extract of Bush marigold leaf. Each treatment had 3 replicates of 10 birds per replicate in a randomized complete block design. Results: The results indicated that feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Dietary manipulations involving nutritional (Oko et al, 2018), sensory, chemical, physical and physiological characteristics of feed materials are part of the innovative strategies developed for improving the quality of animal products (Runjaic-Antic et al, 2010;Agiang et al, 2011). In this study, the results obtained for external egg quality was in agreement with the findings of Oko et al (2018) who used ethanolic extract of Aspilia africana leaf to feed quails, who stated that egg size (9.72 -10.37g).…”
Section: Discussionsupporting
confidence: 83%
“…Dietary manipulations involving nutritional (Oko et al, 2018), sensory, chemical, physical and physiological characteristics of feed materials are part of the innovative strategies developed for improving the quality of animal products (Runjaic-Antic et al, 2010;Agiang et al, 2011). In this study, the results obtained for external egg quality was in agreement with the findings of Oko et al (2018) who used ethanolic extract of Aspilia africana leaf to feed quails, who stated that egg size (9.72 -10.37g).…”
Section: Discussionsupporting
confidence: 83%
“…The highest EN, EP, EW, EM and the best FCR were significantly (p ≀ 0.001) obtained by the group received 200 mg COEx/kg, followed by 250 mg COEx/kg and 120g COP/kg, compared with the control and other groups. These findings are in agreement with those of Agiang et al (2011), who found that daily egg production was enhanced in quails consumed a 5% aqueous extract of bush calendula leaves. The same results were obtained by Nuraini and Djulardi (2016) who mentioned that the levels of marigold flower extract (MFE) in the diet affected (p<0.05) the hen-day egg production of Japanese quails.…”
Section: Serum Biochemistrysupporting
confidence: 93%
“…Quails have been farmed for commercial egg and meat production since 1900 [1]. Its meat and eggs are sources of animal protein with high biological value due to their lower caloric content [2]. In addition, quails have important advantages such as they are growing fast, reaching sexual maturity early, being resistant to disease, producing a high number of eggs, having short generation intervals, and having a short incubation period [3].…”
Section: Introductionmentioning
confidence: 99%